International consensus statement on injury surveillance in cricket: a 2016 update. Issue 20 (8th June 2016) - Orchard, John W; Ranson, Craig; Olivier, Benita; Dhillon, Mandeep; Gray, Janine; Langley, Ben; Mansingh, Akshai; Moore, Isabel S; Murphy, Ian; Patricios, Jon; Alwar, Thiagarajan; Clark, Christopher J; et al.
Abstract : Cricket was the first sport to publish recommended methods for injury surveillance in 2005. Since then, there have been changes to the nature of both cricket and injury surveillance. Researchers representing the major cricket playing nations met to propose changes to the previous recommendations, with an agreed voting block of 14. It was decided that 10 of 14 votes (70%) were required to add a new definition element and 11 of 14 (80%) were required to amend a previous definition. In addition to the previously agreed 'Match time-loss' injury, definitions of 'General time-loss', 'Medical presentation', 'Player-reported' and 'Imaging-abnormality' injuries are now provided. Further, new injury incidence units of match injuries per 1000 player days, and annual injuries per 100 players per year are recommended. There was a shift towards recommending a greater number of possible definitions, due to differing contexts and foci of cricket research (eg, professional vs amateur; injury surveillance systems vs specific injury category studies). It is recommended that researchers use and report as many of the definitions as possible to assist both comparisons between studies within cricket and with those from other sports.